2022
DOI: 10.3389/fbioe.2022.878588
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Healing in Full-Thickness Wound by Chitosan-Binding bFGF and Antimicrobial Peptide Modification Chitosan Membrane

Abstract: Skin wound healing is an important clinical challenge, and the main treatment points are accelerating epidermal regeneration and preventing infection. Therefore, it is necessary to develop a wound dressing that can simultaneously cure bacterial infections and accelerate wound healing. Here, we report a multifunctional composite wound dressing loaded with chitosan (CS)-binding bFGF (CSBD-bFGF) and antimicrobial peptides (P5S9K). First, CS was used as the dressing matrix material, and P5S9K was encapsulated in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Analysis of epithelial thickness was performed using ImageJ software (NIH, United States), where a skilled histologist blindly evaluated the analyses of tissue slices by choosing three random, non-overlapping areas at a magnification of ×10 per tissue section. The epithelial gap as well as percentage of reduction in wound size were measured using four panoramic images of different histological sections following the protocol described by Hou et al (2022) .…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of epithelial thickness was performed using ImageJ software (NIH, United States), where a skilled histologist blindly evaluated the analyses of tissue slices by choosing three random, non-overlapping areas at a magnification of ×10 per tissue section. The epithelial gap as well as percentage of reduction in wound size were measured using four panoramic images of different histological sections following the protocol described by Hou et al (2022) .…”
Section: Methodsmentioning
confidence: 99%
“…After 5 days of treatment, the expression of collagen was significantly increased . In another study, Hou et al also reported that bFGF (500 ng/mL)-bound chitosan membranes could upregulate the expression of collagen after 4 days of treatment . In the present study, we also combined similar concentrations of bFGF (500 ng/mL) with SA microspheres to construct the hydrogel composite to promote collagen expression (Figure ).…”
Section: Discussionmentioning
confidence: 50%
“…66 In another study, Hou et al also reported that bFGF (500 ng/mL)-bound chitosan membranes could upregulate the expression of collagen after 4 days of treatment. 18 In the present study, we also combined similar concentrations of bFGF (500 ng/mL) with SA microspheres to construct the hydrogel composite to promote collagen expression (Figure 6). Jia et al noted a reverse correlation between the concentration of bFGF (10−100 ng/ mL) and the effect on the proliferation of rat adipose mesenchymal stem cells and the expression of collagen after 7 days of stimulation.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Zibai ointment can improve the microenvironment of the wound, keep the wound moist and provide an environment conducive to cell growth and wound healing. And bFGF, as an important growth factor, plays a momentous effect in wound healing [13][14][15]. The wnt/β-catenin signaling pathway has multiple functions in wound healing, including promoting epithelial cell proliferation and migration, promoting angiogenesis, and regulating inflammatory response [16,17].…”
Section: Discussionmentioning
confidence: 99%